Evaluation the Electronic Properties of Glu-Ureido Template via Ab-Initio Study as Target Specific for PSMA - Mohd. Faheem; Vaibhav Pandey; Anjli Shrivastav; Manisha Prasad; Manish Dixit (Chemistry Proceedings, 2024)
The Prostate cancer (PC) is a major problem all over worldwide and this is the second highest cancer-related mortality rate after lung cancer all over worldwide. At least 299,010 likely cases in men were reported in the US in 2024 and about 35,250 deaths are reported. The overexpression of prostate-specific membrane antigen (PSMA) is a key factor in the progression of prostate cancer and contributes to metastasis in lymph nodes, soft tissues and bones metastasis. The numerous studies have reported that, Glu-ureido-based molecules exhibit high binding affinity for PSMA. The earliest imaging agents developed from this structure were labeled with radioactive halogen isotopes and demonstrated nanomolar binding affinity, leading to exceptional imaging properties. Hence the Glu-ureido chemical moiety is a very important template as inhibitor of PSMA. In this study to explore the chemical structural and electronic features of Glu-Ureido structure with the aid of quantum chemistry computer simulations. In this study, first optimized the structure of this chemical structure using the B3LYP 6311-G (++, d, p) basis set. In this study investigated the maximal quantity of electronic charge transfer (Nmax), chemical hardness (η), electrostatic potential, chemical potential (µ) and electrophilicity (ω). By the using Natural Bond Orbital (NBO) analysis, the examination shows that the molecule’s chemically active regions π-electron-electron delocalization within the molecule that contribute to its stability.